Multiscale studies and parameter developments for metal-organic framework Fe-MOF-74 - Moeljadi, Adhitya Mangala Putra (2017)
Metal–Organic Frameworks (MOFs) is class of materials, constructed from an extensive network of coordination polymers that exhibits distinct properties and architectures, depending on the nature of its elementary building unit. Since the introduction of MOFs nearly two decades ago, they have inspired a growing body of research to accomplish practical applications in various scientific and industrial fields. In particular, the design and application of MOFs for gas absorption and storage, gas separation technology as well as selective catalysts are already established and well documented. From computational perspective, an in-depth understanding of chemical processes at a microscopic level can benefit the pursuit of applicability by providing insight as to how to achieve truly exceptional materials. On the other hand, since MOFs feature an extended system with staggering size, it also motivates the development of new theoretical methods that provides accurate description of real systems based on reasonable models. Through this thesis, computational methods such as density functional theory (DFT), molecular mechanics (MM), hybrid quantum mechanics/molecular mechanics (QM/MM) method as well as periodic calculations are developed and applied to some examples of important chemical processes in MOFs. In this thesis, we present our findings as our contribution to the ongoing efforts to utilize computational methods in the field of MOFs.